Frequency Integration of Dual-band Hexagonal Metamaterial Resonator antenna for Wi-Fi and 5G Wireless Communication. Issue 1 (1st April 2022) - Hakim, M L; Alam, T; Baharuddin, M H; Islam, M T
Abstract: The integration of 5G mm-wave and Wi-Fi frequency bands becomes significant for upcoming 5G wireless applications for providing a large frequency ratio. This work presents a frequency reconfigurable hexagonal metamaterial resonator (HMR) antenna for Wi-Fi and a 5G mm-wave frequency band. A PIN diode is utilized to link up a microstrip patch antenna (MPA) with HMR to achieve integration of the Wi-Fi frequency band. The resonant frequency of the proposed antenna is 5 GHz (Wi-Fi) and 27.87 GHz with peak gain 2.33 dB and 7.12 dB, respectively. The operating bandwidth of the proposed antenna is 800 MHz (4.5-5.3 GHz) and 1020 MHz (27.35-28.37 GHz). The rogers RT5880 substrate with thickness 0.508 mm, dielectric constant 2.2, and loss tangent 0.009 has been used for designing the antenna. The overall size of the antenna is 30×23×0.508 mm 3 .